Penerapan Strategi Syariah Dalam Meningkatkan Digital Marketing Pada Usaha Kecil Menengah di Indonesia - Rizka Aulia; Chuzaimah Batubara (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2025)
This study aims to explore the application of sharia strategies in increasing digital marketing in small and medium enterprises (SMEs) in Indonesia. SMEs have an important role to play in the Indonesian economy, but many of them still face challenges in marketing their products and services effectively. The research method used in this study is a qualitative approach using in-depth interviews with a number of SME owners and managers in different sectors. The data obtained was analyzed using a thematic approach to identify emerging patterns and findings. The results of the study show that implementing sharia strategies in digital marketing for SMEs can provide several benefits. Sharia strategies can help SMEs to build a positive and credible image in the eyes of Muslim consumers who are sensitive to religious values. Sharia strategy can help SME's relationship with customers stronger through an approach that is based on fairness, and honesty. Sharia strategies can also motivate SMEs to innovate in developing products or services that are in accordance with Islamic values, so as to attract wider consumer interest. The implication of this research is the importance of a holistic and integrated approach in implementing sharia strategies in digital marketing, as well as the importance of support from the government, financial institutions and educational institutions in increasing the understanding and access of SMEs to this strategy.